Metal-organic frameworks activate the cGAS-STING pathway for cancer immunotherapy - Shuxuan Zhu; Wenfei Xu; Hongxia Li; Zhaogang Sun; Ying Zhu; Wenjing Liu; Hongqian Chu (Journal of Nanobiotechnology)
Abstract Despite the major breakthroughs in immunotherapy, a substantial number of cancer patients continue to confront problems such as low response rates, which restrict the overall effectiveness of existing treatments. There is an urgent necessity to combine advanced biomedical advancements with conventional therapies to improve treatment results. The activation of the cyclic GMP-AMP synthase (cGAS) and stimulator of interferon genes (STING) pathway has become a viable technique to elicit innate immune responses against tumors, attracting significant interest as a novel target in cancer therapy. However, STING agonists face significant challenges in clinical application due to complications related to transport efficiency, degradation, and bioavailability. Recent breakthroughs in nanotechnology have facilitated the invention of metal-organic frameworks (MOFs) as adaptable platforms for cancer immunotherapy, utilizing their distinctive characteristics, including large surface area, adjustable porosity, and improved permeability. This review systematically investigates current advancements in the usage of MOFs for altering the cGAS-STING pathway, highlighting their promise as adaptable platforms for agonist administration or direct activation in tumor immunotherapy. Additionally, this review focuses on the use of MOFs as carriers or agonists, integrated with multimodal strategies to potentiate anticancer immune responses via the cGAS-STING pathway. The discussion concludes with an examination of the challenges and future directions for MOFs in boosting immunotherapy through the stimulation of the cGAS-STING pathway. Graphical abstract